Al2O3:C and Al2O3:C, Mg optically stimulated luminescence 2D dosimetry applied to magnetic resonance guided radiotherapy. (November 2020) - Shrestha, N.; Yukihara, E.G.; Cusumano, Davide; Placidi, Lorenzo
Abstract: The objective of this work is to demonstrate the potential application of Al2 O3 :C and Al2 O3 :C, Mg optically stimulated luminescence (OSL) films for 2D dosimetry in magnetic resonance guided radiotherapy (MRgRT), a modality which combines two dosimetric challenges: small field dosimetry and dosimetry in the presence of a magnetic field. To achieve that, prototype Al2 O3 :C and Al2 O3 :C, Mg OSL films produced by Landauer (Glenwood, IL, USA) were characterized using a MRIdian system (ViewRay Inc., Mountain View, California, USA). The system was initially equipped with three 60 Co heads on a ring gantry combined with a 0.35 T split-magnet MRI system and later upgraded with a 6 MV Flattening Filter-Free (FFF) linear accelerator, with a fixed dose rate of 600 MU/min. The dosimetric properties of the film material (Al2 O3 :C) in the magnetic field were first tested by irradiating samples of 7 mm in diameter read using a Risø TL/OSL automated reader for high precision. OSL films (Al2 O3 :C and Al2 O3 :C, Mg) were then tested at different doses and for two different intensity modulated radiation therapy (IMRT) treatment plans, for which the gamma analysis was performed using the 2D dose information obtained by readout of the films using a laser-scanning OSL reader. The results using the "point-dosimeter" samples showed deviations <4% with the delivered dose and variations within the same package of <4% (standard deviation of the data). The gamma analysis for IMRT plans showed pass rates >95% with a 3% - 3 mm criteria (>84% with a 2% - 2 mm criteria), with the failure typically happening in the edges of the film, not in the central high dose region. The results did not show any clear influence of the magnetic field and demonstrate the feasibility of Al2 O3 :C and Al2 O3 :C, Mg OSL dosimeters for 2D dosimetry in MRgRT.